Enhanced supply of methionine or arginine alters mechanistic target of rapamycin signaling proteins, messenger RNA, and microRNA abundance in heat-stressed bovine mammary epithelial cells in vitro (2019)
ABSTRACT: Heat stress (HS) causes reductions in milk production, but it is unclear whether this effect is due to reduced number or functional capacity (or both) of mammary cells. Methionine supplementation improves milk protein, whereas Arg is taken up in excess by mammary cells to produce energy and nonessential AA that can be incorporated into milk protein. To evaluate molecular mechanisms by which mammary functional capacity is affected by HS and Met or Arg, mammary alveolar (MAC-T) cells were incubated at thermal-neutral (37°C) or HS (42°C) temperatures. Treatments were optimal AA profiles (control; Lys:Met = 2.9:1.0; Lys: Arg = 2.1:1.0), control plus Met (Lys:Met = 2.5:1.0), or control plus Arg (Lys:Arg = 1.0:1.0). After incubation for 6 h, cells were harvested and RNA and protein were extracted for quantitative real-time PCR and Western blotting. Protein abundance of mechanistic target of rapamycin (MTOR), eukaryotic initiation factor 2a, serine-threonine protein kinase (AKT), 4E binding protein 1 (EIF4EBP1), and phosphorylated EIF4EBP1 was lower during HS. The lower phosphorylated EIF4EBP1 with HS would diminish translation initiation and reduce protein synthesis. Both Met and Arg had no effect on MTOR proteins, but the phosphorylated EIF4EBP1 decreased by AA, especially Arg. Additionally, Met but not Arg decreased the abundance of phosphorylated eukaryotic elongation factor 2, which could be positive for protein synthesis. Although HS upregulated the heat shock protein HSPA1A, the apoptotic gene BAX, and the translation inhibitor EIF4EBP1, the mRNA abundance of PPARG, FASN, ACACA (lipogenesis), and BCL2L1 (antiapoptotic) decreased. Greater supply of Met or Arg reversed most of the effects of HS occurring at the mRNA level and upregulated the abundance of HSPA1A. In addition, compared with the control, supply of Met or Arg upregulated genes related to transcription and translation (MAPK1, MTOR, SREBF1, RPS6KB1, JAK2), insulin signaling (AKT2, IRS1), AA transport (SLC1A5, SLC7A1), and cell proliferation (MKI67). Upregulation of microRNA related to cell growth arrest and apoptosis (miR-34a, miR-92a, miR-99, and miR-184) and oxidative stress (miR-141 and miR-200a) coupled with downregulation of fat synthesis-related microRNA (miR-27ab and miR-221) were detected with HS. Results suggest that HS has a direct negative effect on synthesis of protein and fat, mediated in part by coordinated changes in mRNA, microRNA, and protein abundance of key networks. The positive responses with Met and Arg raise the possibility that supplementation with these AA during HS might have a positive effect on mammary metabolism.